Influencia de phet interactive simulations en la enseñanza- aprendizaje del movimiento parabólico en los estudiantes de segundo año de bachillerato general unificado de la Unidad Educativa “Ángel Polibio Chaves”, del cantón Guaranda, provincia Bolívar, durante el período (noviembre 2022 – marzo 2023). - Verdezoto Ramos, Nelson Joel (2023)
The purpose of the curricular integration project is to demonstrate the influence of PhET Interactive Simulation in the teaching-learning of the second-year students of the unified general baccalaureate of the educational unit "Ángel Polibio Chaves" in the city of Guaranda, which entails great challenges to when it comes to teaching the physics chair, this being one of the most complicated subjects to understand in teenagers who are studying this subject and in this way not only reach the student but in order to promote the use and importance of virtual laboratories for teach educational content that is related to the area of physics. This one research project was carried out through a quantitative approach due to the use of technological tools that allowed us to obtain statistical results in terms of learning in the subject of physics, data collection techniques and instruments were also implemented that facilitated the understanding of the main objective. to give a proposal according to the investigation because this arises with the problem of traditional education that has not evolved as it should be in recent times and with the advancement of technology we must instill these new tools in education. All this research process converged to the development of a PhET virtual laboratory manual specifically in the physics area to understand the parabolic motion of an object in 2,, in different ways, with which the student and the teacher will be able to interact with this software in a dynamic, didactic and understandable way